Poverty Alleviation as a Social Welfare Policy: Implementation of the Saraswati Program for the Benefit of Society - Irawati, Shinta Tris (LP2M INSURI Ponorogo, 2025)
Sragen Regency has the highest percentage of poor people in Solo Raya. Despite the highest percentage of poor people, efforts to accelerate poverty reduction are in the second highest place in Solo Raya. These efforts are carried out by implementing poverty alleviation policies through the Saraswati Program. The focus of the research is to analyze the implementation of the poverty alleviation policy of the Saraswati Program as a social welfare policy and its beneficial elements for policy recipients. The research approach is qualitative. Interviews were conducted with 12 informants through purposive sampling techniques. The results of the study show that poverty alleviation of the Saraswati Program through the perspective of social welfare policy in the basic aspect of policy has applied the concept of selectivity, the aspect of the type of policy is carried out through the provision of direct services, the aspect of the funding system is carried out by utilizing the APBD, and the distribution aspect is carried out directly to the beneficiaries. Poverty alleviation policies bring benefits in providing social welfare services. Still, there is not yet a full monitoring process in the implementation process, so it is expected that it is necessary to carry out these stages to get a more effective benefit impact.